Possibilidades da programação de computadores para o desenvolvimento da percepção musical : uma análise a partir da utilização do Scratch - Horas, Jean Leandro (2021)
Considering the changes that happen in the world due to the popularization of digital technologies, the educational scenario has to keep up with these transformations in a way to use resources that facilitate and make the educational processes more dynamic and that could promote new ways of interaction. Thus, music as a compromised source for sensitivity and humanization of people, becomes the possibility for reframing interpersonal relations and to develop discerning, independent and conscious individuals about their social responsibility and educational integrality. Therefore, this study discusses the concept of musicality as a way of developing and enhancing the meaning of sounds, enabling the enlargement of musical knowledge. Digital technologies arise as a methodological alternative for musical development that goes beyond the use of musical instruments physically. So, computer programming, through the use of the Scratch® software, is analyzed in this research in a way to verify the applicability of this software in the promotion of musical perception in children. Therefore, the motion of this study was: “Which are the possibilities of computer programming for the development of musical perception in children?” Also, the objective of this research is to evaluate an experience of musical perception improvement based in a computer programming sequence. In order to answer the motion of this master’s dissertation, regarding the given objectives, the structure of the text was organized between two theoretical chapters, besides the methodological draft, report and analysis of the empirical research. So, the first theoretical chapter approaches musicality as a way of expanding and improving the meaning of sounds, which contributes to an integral education scenario. The second chapter discusses the possibilities of computer programming for the enhancement of musical development, approaching technology as a dynamic and alternative for teaching music. As theoretical foundation, authors such as Maffioletti (2001), Swanwick (2003), Mársico (2003), Pereira (2006), Papert (1994), Bastos, Borges and D’Abreu (2010), Brackmann (2017), Masetto (2015), Silva (2015), among others, were used. The methodology of the study was set as a qualitative, bibliographic, and of research-action approach. The empiric research, performed remotely on account of the pandemic of COVID-19, had students of the 5th grade of a privet school in Frederico Westphalen town, Rio Grande do Sul state, Brazil, as a target audience. The experience was performed in six meetings, in which the Scratch® software was used as tool for musical development. Thus, it is concluded that the musical development of the students was improved, leading to the evidence that computer programming allows musical learning, once the use of Scratch® software helped the children to explore several important musical elements through a playful, engaging and alternative platform.